Study of Knock Sensors as Low-Cost Alternatives to Acoustic Emission Sensors - Fernandez, Breno O. (2020)
The real-time monitoring of manufacturing processes is essential to achieve high-quality standards and uniformity at reduced costs. The monitoring of machining processes is usually performed by acoustic emission sensors, which measure the dynamic waves of mechanical stress that propagate through the material during the grinding process. This work studies the application of knock sensors, commonly used in the monitoring of combustion engines, as a low-cost and high-robustness alternative to acoustic emission sensors in the monitoring of the grinding process. Built to operate mechanically attached to the engine block, the knock sensor is resistant to high temperatures, liquids, and particles. In order to demonstrate the feasibility of the sensor, different tests were performed. By determining its resonant frequency, it was possible to identify the response curve of the sensor and its optimal operating range. The acoustic impulse test, generated by the pencil lead break technique, allowed the comparative analysis of the spectral performance between the acoustic emission sensor and the knock sensor. The performance of the knock sensor in an industrial environment was also verified in a case study. The results showed a similar spectral behavior between both sensors when subjected to the same stimulus, demonstrating the feasibility of using the knock sensor to monitor the grinding process.